ALK gene rearranged lung adenocarcinomas: molecular genetics and morphology in cohort of patients from North India. Issue 10 (8th August 2016) - Bal, Amanjit; Singh, Navneet; Agarwal, Parimal; Das, Ashim; Behera, Digambar
Abstract : ALK gene rearrangement in the lung adenocarcinomas is the second most common (1.6–11.7% of NSCLC) targetable genomic change after EGFR mutations. However, the prevalence and clinicopathological features of ALK ‐rearranged lung adenocarcinomas from North India are lacking. A total of 240 cases of lung adenocarcinoma were screened for EGFR mutations and for ALK expression. Smoking status, TNM stage, and treatment response were recorded in all cases. Out of 240 cases screened, 37 cases were positive for EGFR mutations and 17 cases (7.08%) showed ALK positivity with immunohistochemistry and break‐apart FISH. On excluding 37 EGFR mutation–positive cases, the incidence of ALK ‐positive adenocarcinoma appears to be higher (17/203 cases, 8.03%). Eight were men and nine were women with mean age of 51.7 years. Majority (62.5%) were non‐smokers and had unresectable disease (70.6% stage IV, 17.6% IIIB). The morphological patterns noted were solid (12 cases), papillary (four cases), and micropapillary (one case). Signet ring (two cases) and clear cell change (one cases) were noted. Out of five patients who received crizotinib, three had partial response and two had stable disease. ALK ‐rearranged lung adenocarcinomas account for a minor proportion of NSCLC with prevalence similar to that reported in literature. However, as contrast to published data in our series, patients were in older age group and had solid and papillary pattern on morphology with an aggressive course.